The Rate of Magnetic Resonance Imaging in Patients With Spinal Cord Stimulation - Desai, Mehul J. (Spine (Phila Pa 1976), 2015)
STUDY DESIGN. Analysis of use of magnetic resonance imaging (MRI) in the chronic back and leg pain spinal cord stimulation (SCS)–implanted population was conducted using a propensity-matched cohort population. OBJECTIVE. To project the percentage of patients with SCS expected to need at least 1 MRI within 5 years of implant. SUMMARY OF BACKGROUND DATA. Patients experiencing pain, including those who underwent implantation with SCS systems, are likely to have comorbidities and ongoing pain issues that may require diagnostic imaging. MRI is the most common diagnostic imaging modality for evaluating patients with new or worsening low back pain. However, patients with SCS are typically excluded from receiving MRI because of the safety risks related to the interactions of MRI fields and implantable devices. METHODS. To provide an accurate estimate of the need for MRI in the SCS-implanted population, Truven Health MarketScan Commercial Claims and Medicare Supplemental databases were used to perform analysis of SCS-implanted patients propensity score matched to a nonimplanted population–based cohort. Four years of paid and adjudicated claims data were used to determine the magnetic resonance (MR) images received, which was exponentially projected to estimate MRI within 5 and 10 years of implant. RESULTS. Approximately 82% to 84% of SCS-implanted patients are expected to need at least 1 MRI within 5 years of implant. Furthermore, 59% to 74% of patients will require nonspine MRI within 10 years. CONCLUSION. There is a high need for MRI in this chronic back and leg pain SCS population, with a significant portion being completed on locations outside of the spine. This analysis highlights a need for MRI-conditional SCS devices that grant access of patients with SCS to this imaging modality. Level of Evidence: 3